Fuel cells and hydrogen : from fundamentals to applied research - Hacker, Viktor; Mitsushima, Shigenori (Elsevier, 2018)
Fuel Cells and Hydrogen: From Fundamentals to Applied Research provides an overview of the basic principles of fuel cell and hydrogen technology, which subsequently allows the reader to delve more deeply into applied research. In addition to covering the basic principles of fuel cells and hydrogen technologies, the book examines the principles and methods to develop and test fuel cells, the evaluation of the performance and lifetime of fuel cells and the concepts of hydrogen production. Fuel Cells and Hydrogen: From Fundamentals to Applied Research acts as an invaluable reference book for fuel cell developers and students, researchers in industry entering the area of fuel cells and lecturers teaching fuel cells and hydrogen technology.